INFANTILE HERPES ZOSTER - Serra, David (2011)
We report a case of herpes zoster in a 10-month old male infant. This otherwise healthy boy had no prior history of varicella and parents denied any exposure to varicella-zoster virus (VZV) during pregnancy. A household exposure to varicella occurred at 1 month of age. A diagnosis of herpes zoster was established on clinical grounds and confirmed by serological assays. He was treated with oral acyclovir, with complete resolution of lesions without sequelae. Clinical and laboratorial evaluation did not uncover any underlying illness. In this setting, we discuss some peculiar aspects of VZV infection in this age group and review current recommendations for the management of herpes zoster in pediatric patients.